2014
DOI: 10.1088/0964-1726/23/7/077003
|View full text |Cite
|
Sign up to set email alerts
|

A novel triple-actuating mechanism of an active air mount for vibration control of precision manufacturing machines: experimental work

Abstract: With the goal of vibration control and isolation in a clean room, we propose a new type of air mount which consists of pneumatic, electromagnetic (EM), and magnetorheological (MR) actuators. The air mount is installed below a semiconductor manufacturing machine to reduce the adverse effects caused by unwanted vibration. The proposed mechanism integrates the forces in a parallel connection of the three actuators. The MR part is designed to operate in an air spring in which the EM part is installed. The control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The hybrid mounts was composed of an air spring and an MR damper for isolation and absorption, respectively. The MR damper can generate 415 N of damping force in resonance conditions, and its working distance was ±5 mm [10,11]. The sealing of MR fluid was a major issue in design because of working distance and nonlinear elasticity.…”
Section: The Motion Stage and Hybrid Mountsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hybrid mounts was composed of an air spring and an MR damper for isolation and absorption, respectively. The MR damper can generate 415 N of damping force in resonance conditions, and its working distance was ±5 mm [10,11]. The sealing of MR fluid was a major issue in design because of working distance and nonlinear elasticity.…”
Section: The Motion Stage and Hybrid Mountsmentioning
confidence: 99%
“…When an MR damper is used with an isolator, it is called a hybrid mount. Seong et al proposed an MR damper installed in a hybrid mount system [10], and Kim et al proposed a hybrid mount system by integrating an MR damper with an EM actuator [11]. Most of the hybrid structures have been based on a parallel connections, but Zhu proposed a serial connection of MR damper and an isolator [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the past 20 years, the significant advantages of MR fluids, such as their fast reactivity and easy controllability in terms of high yield stress, have been utilized in various devices including dampers [3], valves [4], brakes [5], clutches [6], mounts [7][8][9], and even medical devices [10]. In particular, it has been reported that MR dampers are applicable to many different industries in terms of a reduction of unwanted vibrations and impact, including in vehicle suspensions (for passenger [11][12][13], military [14], and railway [15] vehicles), landing gear systems [16], seat dampers [17,18], washing machines [19,20], industrial machines [21,22], seismic response reduction structures [23,24], bridge vibration control [25], impact absorbers for gun recoil systems [26], vehicle crash energy absorbers [27,28], pedestrian protection systems in vehicles [29], and shock profile systems [30].…”
Section: Introductionmentioning
confidence: 99%
“…A conventional passive-isolation scheme has to make a reasonable compromise between attenuation at high frequency and amplification at resonance due to the intrinsic limitations of fixed stiffness and damping parameters. To cope with this problem, active, semi-active, and hybrid solutions have been sought to develop tunable vibration mounts with variable dynamic characteristics [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%